Regulating the Performance of Lithium-Ion Battery Focus on the Electrode-Electrolyte Interface - Zhao, Dongni; Li, Shiyou (Frontiers in Chemistry, 2020)
The development of lithium-ion battery (LIB) has gone through nearly 40 year of research. The solid electrolyte interface film in LIBs is one of most vital research topics, its behavior affects the cycle life and safety of LIBs significantly. Progress in understanding the interfacial layer on the negative and positive electrodes in LIBs has been the focus of considerable research in the past few decades, but there remains a number of problem to be understood at the fundamental level, and there is still a great deal of controversy regarding the composition and formation mechanism of the interfacial film. In this article, we summarize recent research conducted on the interfacial film in LIBs, including the film formation mechanism, the composition, and stability of the interfacial film on the positive electrodes (in both diluted and high-concentration electrolytes). And the methodologies and advanced techniques implemented for the characterization of the interfacial film. Finally, we put forward some of the future development direction for the interfacial film and urgent problems that need to be solved.